Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe The Power of Two terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VII SMP Negeri 22 Padang - REZA AULIA (Departemen Matematika, 2019)
Good learning outcomes make things important for students. However, the thing that is often faced in learning mathematics is the low learning outcomes of students. The learning outcomes of students of class XI MIPA SMA 3 Bukittinggi are still relatively low and the learning process has not been carried out optimally. The solution applied is the TSTS type of cooperative learning model. The purpose of this study is to describe the difference in learning outcomes of students who study with the cooperative learning model TSTS type with students who learn by direct learning and describe the development of learning activities of students who learn with cooperative learning models of TSTS type in the XI MIPA class of SMA Negeri 3 Bukitiinggi..This type of research is quasy experiment and research design of Static Group Design. The population of this research is the students of class XI MIPA of SMA Negeri 3 Bukittinggi. The sampling technique uses Simple Random Sampling Data technique so that the class XI MIPA 1 is obtained as an experimental class and XI MIPA 3 as a control class. Collecting data in research through student learning activities and final test data in the form of learning outcomes tests that are analyzed by t test.Based on the results of the study showed the learning activities of students tended to increase after the TSTS type of cooperative learning model was applied. Based on the analysis of the final test results was obtained at the real level ???? = 0.05 which means that the learning outcomes of students who applied the TSTS type of cooperative learning model were better than those of students learning with direct learning in the XI MIPA class of SMA 3 Bukittinggi, therefore, it can be concluded that there is a significant influence on the application of the TSTS type cooperative model to the learning outcomes of students of the XI MIPA grade 3 SMA Negeri Bukittinggi.Keywords – TSTS (Two Stray Two Stray, learning outcomes)